Variation in rain drop size distribution and rain integral parameters during southwest monsoon over a tropical station: An inter-comparison of disdrometer and Micro Rain Radar - Jash, Dharmadas; Resmi, E.A.; Unnikrishnan, C.K.; Sumesh, R.K.; Sreekanth, T.S.; Sukumar, Nita; Ramachandran, K.K. (Atmospheric research, 2019)
The study focuses on the inter-comparison of rain drop size distributions (DSD) and rain integral parameters retrieved using continuous observations from Micro Rain Radar (MRR) and Optical Disdrometer (OD). The variations of the rain parameters during the southwest monsoon period of 2012 over a tropical coastal station are examined. The rain rate and radar reflectivity obtained from both MRR and disdrometer show a correlation of ~0.9. Observations from both the instruments do show that rain intensity of ~2 mm h−1 contributes maximum towards the accumulated rain water. Rain rates are classified into six rain categories to understand the variation with rain intensity. For each rain rate regime, DSDs from MRR and disdrometer compare well for ~1–3 mm diameter range. On the other hand, at larger drop diameters (above D ~ 3 mm) disdrometer overestimates number concentration and at smaller diameters (below D ~ 0.7 mm) disdrometer underestimates number concentration. RD (integrand of rain rate integral) follows a bell-shaped distribution in which the peak position shifts between 1-2 mm drop diameter and widens along with each rain class. Profiles of DSD in Bright Band (BB) and Non-Bright Band (NBB) cases demonstrate that the BB rain events are associated with higher number concentration of larger drops and NBB events are associated with higher concentration of smaller drops. The vertical profile of RD explains that in BB conditions D ~ 1.3 mm significantly contributes total rain water content and for NBB contribution arises from D ~ 1.1 mm at surface level. The profiles also show smaller drops (<1 mm) are found prominent above 2 km towards the rain water content. The Z-R relationships calculated using SIFT method that reduces the scatters in the relation shows good agreement between MRR and disdrometer for the coefficient and exponent values. The relation found for BB(NBB) is Z = 355R1.42(Z = 215R1.46) from disdrometer and those found from MRR is Z = 367R1.37(Z = 211R1.44). The exponent values of Z-R profile (well within 1 ≤ b ≤ 1.63) for BB case represents the DSD spectra are evolved through mixed controlled processes whereas NBB cases are dominated by size-controlled processes. The study reveals that in heavy rainfall conditions there is significant disparity in rain integral parameters between disdrometer and MRR measurements which arises due to the laser inhomogeneity problem of disdrometer, difference in measurement principles and the attenuation of MRR signal at different altitude levels. •DSDs compare well for rain drop diameters in the range 1-3 mm from disdrometer and MRR.•Integrand of rain rate integral (RD) follows a bell-shaped distribution and the peak position shifts between 1-2 mm.•For different rain categories the DSD spectra intercept at D~1-2 mm for both MRR and disdrometer observations.•The total rain water content for BB (NBB) cases is significantly contributed by drop diameter, D~1.3 mm (1.1 mm).